2014
DOI: 10.1021/ic502159x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Cross-Linked Porous Protein Crystal Containing Ru Carbonyl Complexes as a CO-Releasing Extracellular Scaffold

Abstract: Protein crystals generally are stable solid protein assemblies. Certain protein crystals are suitable for use as nanovessels for immobilizing metal complexes. Here we report the preparation of ruthenium carbonyl-incorporated cross-linked hen egg white lysozyme crystals (Ru·CL-HEWL). Ru·CL-HEWL retains a Ru carbonyl moiety that can release CO, although a composite of Ru carbonyl-HEWL dissolved in buffer solution (Ru·HEWL) does not release CO. We found that treatment of cells with Ru·CL-HEWL significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 69 publications
0
60
0
Order By: Relevance
“…Such effects may originate from HSA-Ru(CO) 2 complexes serving as temporary CO storage molecules. Compatible with this notion, binding of Ru(CO) n fragments, with n ranging from 0 to 3, typically to histidine, has been described (Santos-Silva et al, 2001; Santos et al, 2012; Seixas et al, 2015; Tabe et al, 2015; Valensin et al, 2010). Moreover, Tabe et al (2015) observed CO release from ruthenium carbonyl-incorporated cross-linked hen egg white lysozyme (HEWL).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such effects may originate from HSA-Ru(CO) 2 complexes serving as temporary CO storage molecules. Compatible with this notion, binding of Ru(CO) n fragments, with n ranging from 0 to 3, typically to histidine, has been described (Santos-Silva et al, 2001; Santos et al, 2012; Seixas et al, 2015; Tabe et al, 2015; Valensin et al, 2010). Moreover, Tabe et al (2015) observed CO release from ruthenium carbonyl-incorporated cross-linked hen egg white lysozyme (HEWL).…”
Section: Discussionmentioning
confidence: 98%
“…Compatible with this notion, binding of Ru(CO) n fragments, with n ranging from 0 to 3, typically to histidine, has been described (Santos-Silva et al, 2001; Santos et al, 2012; Seixas et al, 2015; Tabe et al, 2015; Valensin et al, 2010). Moreover, Tabe et al (2015) observed CO release from ruthenium carbonyl-incorporated cross-linked hen egg white lysozyme (HEWL). Loss or release of a carbonyl moiety, however, does not necessarily imply release of CO because CORM-3-mediated adduct formation to HEWL, HSA, and hemoglobin was also shown to result in the release of CO 2 (Santos-Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…These two steps can only be explained as a subsequent binding of two inhibitor molecules to the two different sites on the enzyme. 52 In contrast, to reproduce the curves in the presence of pyrithione (LB) and 2B only one slow irreversible step is needed (k 6 ), since the initial rate is inhibitor independent. A suitable candidate in AKR1C enzymes would be the His53 (PDB code 3NTY) which is on the surface, but only two residues away from the main catalytic Tyr55.…”
Section: The Ruthenium Complexes 1a and 1b Inhibit Akr1c1-akr1c3 Enzymesmentioning
confidence: 99%
“…10f ). 76 The CO-releasing reaction was achieved by immobilization of a [cis-Ru(CO) 2 X 4 ] 2− unit at Asp18 in the Ru·CL-HEWL as confirmed by X-ray structural analysis (Fig. 10g).…”
Section: Biomolecular Templatesmentioning
confidence: 78%
“…Ueno and co-workers constructed supramolecular proteins for CORM-2 using the ferritin (Fr) cage, 75 hen-egg white lysozyme (HEWL) crystals, 76 and cypovirus polyhedra crystals (PhCs). 77 The Fr cage, which has an outer diameter of 12 nm, provides accumulation sites for Ru carbonyl moieties in the inner cavity (Fig.…”
Section: Biomolecular Templatesmentioning
confidence: 99%